Insects found in birds’ nests from Argentina: Anumbius annumbi (Vieillot, 1817) (Aves: Furnariidae) - Turienzo, Paola; Iorio, Osvaldo Di (Zootaxa, 2008)
Insects found in the nests of Anumbius annumbi (Vieillot) [Aves: Furnariidae] from the provinces of Buenos Aires, Santa Fe, Entre Ríos, and La Pampa (Argentina) were studied. A total of 20 nests was sampled every 21 days in Buenos Aires, together with the insects found under ritidome of Eucalyptus in the same area. Samples from nests were divided by seasons: end of summer [nest 1]; autumn [nests 2 to 6]; winter [nests 7 to 12]; spring [nests 13 to 16]; summer [nests 17 to 19], and beginning of autumn [nest 20]. A total of 92 species of insects was found, of which only 36 species had been previously reported in the literature from 1943 until 2005. Additional nests were sampled from Santa Fe (3 nests), Entre Ríos (1 nest), and La Pampa (4 nests). Species richness, abundance and diversity per nest are given and discussed. Insects in birds´nests are classified according to their functional guilds (predators; hematophages and parasitoids; detritivores; phytophages and fungivorous); degree of permanence in the nests (temporal inhabitants [hibernants]; permanent inhabitants; accidentals and/or occasionals). Mortality among the insect fauna inside the nests and other dead insects found inside nests, probably prey remains, are cited. The insect fauna under the ritidome of Eucalyptus permits establishment of a habitat gradient: species only found in the nests, species mainly found in the nests and rarely under the ritidome, species found both under the ritidome and in the nests, species mainly found under ritidome and seldom in the nests, and species only found under the ritidome. Comments and remarks are made on selected taxa lacking or with limited biological data. The microhabitat in the tunnels of Ctenomys [Rodentia] is compared with the birds’nests regarding its similar insect fauna. Inquiline birds and mammals are also mentioned.